Role of universities in social responsibility and university extension: case UNMSM - Melgarejo Estremadoyro, Gladys Giovanna (2022)
Social Responsibility and University Extension is one of the three substantive functions of the university that, together with teaching and research, aims to promote training and professional development and the transfer of knowledge of the university with its environment in economic development, social and cultural of the society. In this context, with the approval of the University Law, it is emphasized through the University Social Responsibility (RSU) to require all universities to mainstream and integrate their training and research functions with this social role, in connection with their environment and commitment to sustainable development and well-being of society. Therefore, through this article, it is intended to demonstrate this social role of universities "which is going from being an isolated institution to being inserted in the center of the knowledge society, and committed to social transformation" (García, 2014, p. 5).